PENGARUH MODEL PEMBELAJARAN SSCS TERINTEGRASI STRATEGI MERINGKAS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Susana Jelita; Yusnaeni Yusnaeni; Arini Rahma Dhani (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aimed to determine the differential impact of implementing the Search, Solve, Create, and Share (SSCS) learning model—integrated with a summarizing strategy—on the critical thinking skills of Grade XII students at SMA Negeri Harekakae, Malaka Regency, during the 2025/2026 academic year. This quasi-experimental study employed a pretest-posttest control group design. Two classes participated: an experimental class taught using the SSCS model integrated with the summarizing strategy, and a control class taught using conventional methods. The sample was selected via random sampling. The research instrument consisted of essay questions aligned with critical thinking indicators, yielding the following average posttest scores: simple explanation (14.05), basic skills (13.75), advanced explanation (10.42), strategies and techniques (9.90), and inference (11.15). The results showed that the control class achieved an average posttest score of 43.38 (an increase of 10.31), while the experimental class achieved 58.95 (an increase of 31.35). Subsequent data analysis using the non-parametric Mann-Whitney test yielded a significance value of 0.000 (<0.05); thus, it can be concluded that the SSCS learning model integrated with the summarizing strategy effectively enhances the critical thinking skills of Grade XII students at SMA Negeri Harekakae, Malaka Regency.